The Hegemon in Denial? China’s Reluctant Hegemony, BRICS and Southern Leadership - Alyaa, Nisriinaa; Azis, Aswin Ariyanto (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2026)
China’s rising global influence marks a shift in how power operates on the world stage. While traditional theories like Hegemonic Stability Theory (HST) associate leadership with dominance and order maintenance, China challenges this model. Rather than replacing the U.S. as the sole global leader, China is strengthening its structural power through platforms like BRICS, projecting itself as a cooperative, non-imposing actor. This study employs qualitative analysis of strategic norms, pragmatic interests, and institutional projection to evaluate whether existing hegemonic frameworks remain adequate. This paper argues that HST, as a classical framework, is no longer sufficient to capture the evolving nature of hegemony in a fragmented world order. In response, this study introduces the concept of “reluctant hegemony” to explain how China fulfills key hegemonic functions while simultaneously resisting being labeled as a hegemon. The novelty of this research lies in its effort to reconceptualize hegemony through China’s alternative approach: one that neither mirrors U.S. primacy nor entirely rejects leadership, but instead redefines it in accordance with its own strategic principles and normative preferences. These insights contribute to current debates on multipolarity and the reimagining of global governance beyond Western-centric paradigms. Keywords: BRICS, China, Global Governance, Leadership, Reluctant Hegemony Meningkatnya pengaruh global Tiongkok menandai pergeseran dalam cara kekuasaan beroperasi di panggung dunia. Sementara teori tradisional seperti Teori Stabilitas Hegemoni (TSH) menghubungkan kepemimpinan dengan dominasi dan tanggung jawab untuk menjaga ketertiban, Tiongkok menantang model ini. Alih-alih menggantikan AS sebagai satu-satunya pemimpin global, Tiongkok memperkuat kekuatan strukturalnya melalui platform seperti BRICS, memproyeksikan dirinya sebagai aktor yang kooperatif dan tidak memaksakan. Studi ini menggunakan analisis kualitatif terhadap kepentingan pragmatis, norma strategis, dan proyeksi kelembagaan untuk mengevaluasi apakah kerangka kerja hegemonik yang ada masih memadai. Tulisan ini berpendapat bahwa TSH sebagai kerangka kerja klasik tidak lagi cukup untuk menangkap sifat hegemoni yang terus berkembang dalam tatanan dunia yang terfragmentasi. Sebagai tanggapan, studi ini memperkenalkan konsep “hegemoni yang enggan” untuk menjelaskan bagaimana Tiongkok memenuhi fungsi hegemonik utama dan pada saat yang sama menolak diberi label sebagai hegemon. Kebaruan penelitian ini terletak pada upayanya untuk mengonseptualisasi ulang hegemoni melalui pendekatan alternatif Tiongkok: pendekatan yang tidak mencerminkan keutamaan AS atau sepenuhnya menolak kepemimpinan, tetapi mendefinisikannya kembali sesuai dengan prinsip strategis dan preferensi normatifnya sendiri. Temuan ini berkontribusi pada perdebatan terkini tentang multipolaritas dan penataan ulang tata kelola global di luar paradigma yang berpusat pada Barat. Kata-kata Kunci: BRICS, Tiongkok, Tata Kelola Global, Kepemimpinan, Hegemoni yang Enggan